Nitric oxide potentiation of the homomeric ρ1 GABAC receptor function - Gasulla, Javier (2012)
BACKGROUND AND PURPOSE NO is a highly diffusible and reactive gas produced in the nervous system, which acts as a neuronal signal mediating physiological or pathological mechanisms. NO can modulate the activity of neurotransmitter receptors and ion channels, including NMDA and GABAA receptors. In the present work, we examined whether GABAC receptor function can also be regulated by NO. EXPERIMENTAL APPROACH Homomeric ρ1 GABAC receptors were expressed in oocytes and GABA-evoked responses electrophysiologically recorded in the presence or absence of the NO donor DEA. Chemical protection of cysteines by selective sulfhydryl reagents and site-directed mutagenesis were used to determine the protein residues involved in the actions of NO. KEY RESULTS GABAρ1 receptor responses were significantly enhanced in a dose-dependent, fast and reversible manner by DEA and the specific NO scavenger CPTIO prevented these potentiating effects. The ρ1 subunits contain only three cysteine residues, two extracellular at the Cys-loop (C177 and C191) and one intracellular (C364). Mutations of C177 and C191 render the ρ1 GABA receptors non-functional, but C364 can be safely exchanged by alanine (C364A). NEM, N-ethyl maleimide and (2-aminoethyl) methanethiosulfonate prevented the effects of DEA on GABAρ1 receptors. Meanwhile, the potentiating effects of DEA on mutant GABAρ1C364A receptors were similar to those observed on wild-type receptors. CONCLUSIONS AND IMPLICATIONS Our results suggest that the function of GABAC receptors can be enhanced by NO acting at the extracellular Cys-loop.